PEDOLOGICAL AND FLORAL ASSESSMENT OF SHINGHAR VALLEY (DISTRICT ZHOB) THROUGH MULTIVARIATE TOOLS - A. Ayub; S. S. Ahmad; S. Erum; A. Butt (Journal of Animal and Plant Sciences, 2017)
The distribution of herbaceous plant species and effect of edaphic factors on species distribution was studied to build a correlation between the herbaceous species and environmental parameter through multivariate techniques. Three zones were formed on the basis of forest (Pinus gerardiana) density. Herbaceous vegetation was sampled, identified and classified through Two Way Indicator Species Analysis (TWINSPAN). Soil was analyzed for organic matter, electrical conductivity, pH, moisture content and heavy metals (lead, nickel, copper and zinc).Canonical Correspondence Analysis (CCA) was employed to correlate species diversity and edaphic factors, soil organic matter and zinc content was found to be most overruling edaphic factor in the distribution patterns of herbage. The study will be helpful in conservation and better management of native flora.
Keywords: Multivariate; Quantification; Pinus gerardiana; Edaphic factor; Shinghar